Determinants of Saving Rates in Japan - Aziz, Sekar Anissa Hikmatul; Setyowati, Eni (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze the influence of Gross Domestic Product (GDP), labor force, and interest rates on savings rates in Japan during the period 2017 to 2024 in quarterly. In a dynamic economic context, people's saving behavior is one of the important indicators that influence economic stability and growth.Methodology: The analytical method used in this study is multiple regression analysis with the Error Correction Model (ECM). Data used in this study are sourced from the Bank of Japan, the Ministry of Finance of Japan, and the World Bank.Results: The results show that in the short term, savings rates are significantly influenced by the labor force, where increasing labor force participation implies an increase in income and savings capacity.Applications/Originality/Value: In the long term, savings rates are significantly influenced by Gross Domestic Product (GDP), indicating that increasing national income encourages people to save more. However, interest rates show a negative influence on savings rates, where low interest rates tend to reduce people's incentives to save.